Handsanitizer Stand in Efforts to Prevent Covid -19 Transmission In Pantai Hambawang Village, Mandastana District of Batola - Dewi Kartika Wulandari; DEWI KARTIKA WULANDARI (Borneo Community Development, 2021)
In early 2020 the world was shocked by the outbreak of a new pneumonia that started in Wuhan, Hubei Province which then spread rapidly to more than 190 countries and territories. This outbreak is named Coronavirus Disease 2019 (COVID-19) which is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov-2). Covid-19 can be transmitted from one individual to another through droplets. In addition, people can also become infected by touching a surface that has been contaminated with the Covid-19 virus. Covid-19 prevention efforts can be done by increasing endurance, obeying government orders, exercising, wearing masks, washing hands with soap or using a handsanitizer. During the Covid-19 pandemic, the people in the Pantai Hambawang Village paid less attention to the dangers of this virus, lack of health facilities to prevent them, such as limited places to wash hands because clean water is also limited, and other media such as handsanitizers that are not yet available in Pantai Hambawang Village. The implementation of Handsanitizer Stand technology aims to reduce the risk of spreading the virus from hand to hand. Hand sanitizer Stand model stepped on made of PVC as the main material. The results of the program evaluation show a positive appreciation from the community for the appropriate technology made.